Pemeliharaan Anak Dalam Perspektif Fiqh dan Hukum Positif - Rohidin Rohidin (Jurnal Hukum IUS QUIA IUSTUM, 2005)
Basically, there is no disticntion on classic Figh, on law of the Republic of IndonesiaNumber 1 of the year 1974 on Marriage, and Islamic Law Compilation relate to children care right The distinction is merely on the determination of age limit of mumayyiz. When divorce occurs, children before 12 years old (before mumayyiz) is to be the right of the mother or a close relative to the mother, while the cost of bringing up the children will be the responsibility of the father. In a particular condition, the children care right may move to the father. Even, on Act No. 1/1974 states that the right of one ofthe parents can be with drew if one or both of the parents neglect their duties and perform extremely bad behaviour.